Efisiensi Penyisihan COD Dan Pembentukan Biogas Dalam Pengolahan Sludge IPAL Industri Pulp And Paper Dengan Menggunakan Bioreaktor Hibrid Anaerobik - Dwi Mina Intan Permadi; Adrianto Ahmad; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Sludge waste paper processing industry has a COD concentration reached 45,000 mg / L. When discharged directly into the water, it can pollute the environment because of the quality standards set by the government through KEPMEN LH No. 51 1995 which is the COD of 350 mg / L. This study aimed to reduce levels of COD in wastewater using an anaerobic bioreactor hybrid combining two patterns of growth of the microorganisms suspended on the insulated and attached growth media using the stones as cell immobilization. This study took place in four stages. The first stage is the seeding done by adding 200 mL of waste and provides nitrogen every day and lasts for 10 days. The second stage is using the method of acclimatization waste and dispose of the liquid contents of 200 mL and restocked with a substrate of 200 mL per day. The third stage is a start-up using the substrate that enter into the inlet tank, then the feed flows rate of 4L / day flow through the inlet pipe so that the entry into the reactor, the suspension in the reactor will be decomposed by microorganisms resulting in the formation of biogas. The fourth sage anaerobic bioreactor hybrid continuous with variable feed flow rate is 20 L / day, 10 L / day, 6.67 L / day, 5 L / day, 4 L / day, with a working volume of the bioreactor 20 L / day. The results showed that the removal efficiency of each flow rate was 94.44%, 94.44%, 94.44%, 94.44%, and 94.44% respectively and the average biogas production reached 1153,95 mL. Thus the hybrid bioreactor be one of the alternatives that can be used in treating wastewater which has quite high organic content.Keywords: Anaerobic bioreactor hybrid, rock, sewage, COD, biogas formation.